Katherine Dunham's Global Method and the Embodied Politics of Dance's Everyday. Issue 3 (September 2020) - Bench, Harmony; Elswit, Kate
Abstract : In a 1950 letter, choreographer Katherine Dunham mentions trouble keeping dancers with her troupe "[i]n spite of the fact that we are the only non-subsidized professional group that has remained self-supporting over these years, and in spite of the fact that we are loved and respected all over the world and work more weeks out of the year than any other dance group in existence." Although some of these claims would be challenging to validate empirically, Dunham is not exaggerating when she describes the amount of work it took for her and her dancers to keep going without the benefit of public funding or an enduring private patron. This essay is part of a larger critical mixed methods project on historical dance touring and transmission: Dunham's Data: Katherine Dunham and Digital Methods for Dance Historical Inquiry . We turn here to the scale of the "everyday, " beginning by building a daily itinerary of Dunham's travels so as to understand better the global method necessary for her company's survival, and how the ongoing pursuit of solvency propelled her, her performers, and her work into the world.